Charge Density Dependent Two‐Channel Conduction in Organic Electric Double Layer Transistors (EDLTs). (4th February 2014) - Xie, Wei; Liu, Feilong; Shi, Sha; Ruden, P. Paul; Frisbie, C. Daniel
<x xml:space="preserve">Abstract</x> A transport model based on hole‐density‐dependent trapping is proposed to explain the two unusual conductivity peaks at surface hole densities above 1013 cm−2 in rubrene electric double layer transistors (EDLTs). Hole transport in rubrene is described to occur via multiple percolation pathways, where conduction is dominated by transport in the free‐site channel at low hole density, and in the trap‐site channel at larger hole density. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>